Towards the next generation of CERN radiation monitoring front end ASICs. (1st April 2022) - Mohanan, S Kundumattathil; Boukabache, H.; Perrin, D.; Pfeiffer, U.
Abstract: Radiation monitoring using ionisation chambers spans a wide spectrum of radiation fields from environmental monitors to ambient dose monitors near particle accelerators. Hence the output generated by these sensors can vary from few femtoamperes to microamperes. They require specific front-end electronics that can accurately measure the generated current across a wide dynamic range. This work presents the design of an ASIC that can measure currents from −6 fA to −20 μA without any band switching. By employing two different current measurement methodologies — direct slope measurement method and charge balancing based current to frequency converter method, an accuracy of ±6% is achieved across the entire measurement range. The ASIC was fabricated in the 8 inch fab of TSMC 130 nm technology. The designed ASIC aims to replace the front end electronics of radiation monitors at CERN.